Pain Level in Critical Patients With Sleep Hygiene Care In Intensive Care Unit - Suwardianto, Heru; Sari, Dyah Ayu Kartika Wulan (Universitas STRADA Indonesia, 2019)
Bacground: Complaints in critical patients are an unpleasant experience as long as patients are admitted to the ICU. Critical patients with pain are still common and need collaboration to reduce patients in the ICU.Purpose: The purpose of this study was to determine the Pain Level Description of Critical Patients with Sleep Hygiene Care in the Intensive Care Unit.Method: Research design is descriptive-analytic. The study population was all critical patients in the ICU. The study sample was a portion of critical patients who received 170 sleep hygiene care patients. The sampling technique is purposive sampling. The research variable is a description of the patient's pain level. The research instrument used a questionnaire. Data were collected and analyzed using the frequency distribution method.Result: The results of the pain indicator on the Facial Expression study found that the majority of respondents showed grimacings (46.6%), Body movements study found that most showed restlessness (39.4%), Vocalization found that almost all respondents showed Tolerating ventilator or movement / Talking in normal tone / no sound (72.9%), Muscle tension assessment found that most respondents showed Relaxed as much (51.8%). The results of the study showed that the pain scale based on CPOT of the majority of respondents had mild pain as many as 64 respondents (37.6%).Conclusion: Pain description in critical patients with sleep hygiene care shows that there are still many patients who feel pain and need identification and further intervention to reduce it.